Analisis Linguistik Nilai-Nilai Pendidikan dalam Ayat tentang QurbÄn Surat Ash-ShÄfÄt Ayat 102 - Kosim, Abdul; Arrobi, Jimatul (Addabani: Interdisciplinary Journal of Islamic Education, 2023)
The qurban worship performed by Muslims on a regular basis should be able to improve their quality as a Muslim, thus the qurban worship that is carried out is not only value-free rituals but is able to provide positive value to life as a Muslim. This study aims to take part of the educational values contained in the qurban worship, precisely from the Al-Qur'an letter Ash-Shafat verse 102. The method used in this research is descriptive analysis, namely by observing in detail and in depth the description berqurban from the Qur'an in terms of linguistic and interpretive approaches. The results of this study showed that the educational values of the verse in terms of interaction between a teacher and a student must be able to build a dialogical, open, and calming atmosphere.